2015
DOI: 10.1590/1677-3225v14n4a07
|View full text |Cite
|
Sign up to set email alerts
|

Clinical evaluation of two materials in the restoration of abfraction lesions

Abstract: Aim: To evaluate the clinical performance of a composite resin (CR) and a resin-modified glassionomer cement (RMGIC) for the treatment of abfraction lesions. Methods: Thirty patients with abfraction lesions in at least two premolar teeth were selected and invited to participate in this study. All restorations were made within the same clinical time frame. One tooth was restored with CR Z100 TM (3M, St. Paul, MN, USA), and the other was restored with RMGIC Vitremer TM (3M). The restorations were assessed immedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…Some articles did not report the criteria used. [ 14 , 29 , 39 , 43 , 48 , 50 , 53 , 58 , 60 , 66 , 71 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some articles did not report the criteria used. [ 14 , 29 , 39 , 43 , 48 , 50 , 53 , 58 , 60 , 66 , 71 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the isolation of the operative field, absolute isolation [ 14 , 25 , 26 , 28 , 29 , 35 , 37 – 39 , 48 , 50 , 53 , 58 60 , 65 , 71 , 72 , 75 , 79 , 80 , 82 ] or relative isolation [ 27 , 30 , 31 , 34 , 36 , 42 , 43 , 45 47 , 49 , 52 , 55 – 57 , 61 , 62 , 66 , 68 70 , 76 , 78 , 83 – 85 ] was used, in both the intervention and control materials. The same study showed the use of absolute isolation in one of the evaluated restorative materials and relative isolation in another [ 32 , 33 , 59 , 63 ], whereas some articles did not report the type of isolation used in the clinical study [ 40 , 41 , 44 , 51 , 54 , 64 , 67 , 73 , 74 , 77 , 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the presence of resin among the constituents indicates the potential risk of polymerisation shrinkage that could affect the material adaptation around the cavity walls and margins [51]. Other RMGIC disadvantages include marginal discolouration overtime [52], the increased cost when compared to the conventional GIC in addition to the inability to use RMGIC as an ART sealant when there are no light-cure equipment available [51].…”
Section: Materials Used In Artmentioning
confidence: 99%
“…The sample size estimation was calculated using a priori by G* power 3.1.2 software based on the previous studies (Jyothi et al 2011;Medeiros et al 2015). The minimum size of each group was calculated, following these input conditions into software: α (allowable type I error) 0.05 (5%), β (allowable type II error) 0.20 (20%), and power of the study (1-β) = 80%.…”
Section: Sample Size Calculationmentioning
confidence: 99%